Highly Efficient Blue Emission and Superior Thermal Stability of BaAI(12)O(19):Eu2+ Phosphors Based on Highly Symmetric Crystal Structure - Wei, Yi; Cao, Ling; Lv, Lemin; Li, Guogang; Hao, Jiarui; Gao, Junsong; Su, Chaochin; Lin, Chun Che; Jang, Ho Seong; Dang, Peipei; Lin, Jun (AMER CHEMICAL SOC, 2018)
Highly efficient phosphor materials with superior thermal stability are indispensable for phosphor-converted white light-emitting diodes (pc-WLEDs) solid state lighting. In order to obtain a high quality warm white light, near-ultraviolet (n-UV) chips combined with trichromatic phosphors have be extensively studied. Among them, the development of efficient blue phosphor remains a challenging task. In view of the close correlation between 5d-4f transitions of rare earth ions and the coordination environment of host lattice, many studies have been dedicated to improving the photoluminescence performances by modifying the lattice coordination environment including the lattice rigidity and symmetry. In this work, we reported highly efficient blue-emitting Eu2+-doped BaAI(12)O(19) (BAO) phosphors with excellent thermal stability, which were prepared via the traditional high-temperature solid state reaction routes. According to the X-ray powder diffraction (XRD) Rietveld refinement analysis, BAO owned a highly symmetric layer structure with two Ba polyhedrons, marked as Ba(1)O(9 )and Ba(2)O-10 , respectively. The diffuse reflectance spectra revealed the optical band gap to be 4.07 eV. Due to the suitable optical bandgap, the Eu2+ ions could realize a highly efficient doping in the BAO matrix. The photoluminescence excitation (PLE) spectra for asprepared BAO:Eu2+ phosphors exhibited a broad absorption band in the region from 250 to 430 nm, matching well with the n-UV LED chip. Under the UV radiation, it is highly luminous (internal quantum yields (IQYs) = 90%) with the peak around 443 nm. Furthermore, the color purity of BAO:Eu2+ phosphors could achieve 92%, ascribing to the narrow full width at halfmaximum (fwhm = 52 nm), which was even much better than that of commercially available BAM:Eu 2+ phosphor (color purity = 91.34%, fwhm = 51.7 nm). More importantly, the as-prepared BAO:Eu2+ phosphor showed extra high thermal stability when working in the region of 298-550 K, which was a bit better than that of commercial BAM:Eu2+ phosphors. According to the distortion calculation of Ba crystallographic occupation, the superior thermal stability could be attributed to the highly symmetric crystal structure of BAO host. In view of the excellent luminescence performances of BAO:Eu2+, it is a promising blue-emitting phosphor for n-UV WLED.